Chasing the Identification of ASCA Galactic Objects (ChIcAGO): An X-ray survey of unidentified sources in the galactic plane. 1. Source sample and initial results - Anderson, Gemma; Gaensler, B.; Kaplan, D.; Slane, P.; Muno, M.; Posselt, B.; Hong, J.; Murray, S.; Steeghs, D.; Brogan, C.; Drake, J.; Farrell, S.; et al. (Institute of Physics Publishing, 2014)
We present the Chasing the Identification of ASCA Galactic Objects (ChIcAGO) survey, which is designed to identify the unknown X-ray sources discovered during the ASCA Galactic Plane Survey (AGPS). Little is known about most of the AGPS sources, especially those that emit primarily in hard X-rays (2-10 keV) within the Fx 10-13 to 10-11 erg cm -2 s-1 X-ray flux range. In ChIcAGO, the subarcsecond localization capabilities of Chandra have been combined with a detailed multiwavelength follow-up program, with the ultimate goal of classifying the >100 unidentified sources in the AGPS. Overall to date, 93 unidentified AGPS sources have been observed with Chandra as part of the ChIcAGO survey. A total of 253 X-ray point sources have been detected in these Chandra observations within 3' of the original ASCA positions. We have identified infrared and optical counterparts to the majority of these sources, using both new observations and catalogs from existing Galactic plane surveys. X-ray and infrared population statistics for the X-ray point sources detected in the Chandra observations reveal that the primary populations of Galactic plane X-ray sources that emit in the Fx 10-13 to 10-11 erg cm -2 s-1 flux range are active stellar coronae, massive stars with strong stellar winds that are possibly in colliding wind binaries, X-ray binaries, and magnetars. There is also another primary population that is still unidentified but, on the basis of its X-ray and infrared properties, likely comprises partly Galactic sources and partly active galactic nuclei. © 2014. The American Astronomical Society. All rights reserved.